Exploring the effects of a new lifter design and ball mill speed on grinding performance and particle behaviour: A comparative analysis - Ali Safa; Sahraoui Aissat (Engineering and Technology Journal, 2023)
Ball mills are the leading grinding equipment in the mineral processing industry. Balls are the primary component in the grinding of materials. Lifters lift these balls to the shoulder position before cataracts them to the toe position. Almost all classical theories do not consider the lifter's geometry in calculating the energy consumption of ball mills and focus only on the fill level of the charge, the lifter dimensions, their number, and the mill's rotational speed. To improve the ball mill's performance, a new shape of the lifters was proposed in the present research work. Simulation through the EDEM software and the discrete element method (DEM) was used to predict the particle behaviour and conduct a comparative study on the influence of the lifter geometry and ball mill rotational speed on torque, power draw, and kinetic energy. The validation of our results is evaluated by a confrontation of the experimental tests of discontinuous grinding with a 573 x 160 cm of Bian. The results show that using helical lifters has a more significant effect on the grinding efficiency, the torque, and the power draw of the ball mill. They decrease the wear rate of liners and lifters when mill speeds are extremely high (90%, 100%).